Direct deprotected glycosyl-asparagine ligation. - Doores, K; Mimura, Y; Dwek, R; Rudd, P; Elliott, T; Davis, B (2006)
A simple and efficient synthesis of N-linked glycoamino acids and glycopeptides from deprotected sugars using the Staudinger reaction.